Method of determining the minimum number of stiffeners for stiffened corrugated steel walls. (December 2021) - Feng, Lifei; Sun, Tianshu; Ou, Jinping
Abstract: The ultimate shear resistance of trapezoidal corrugated steel plate shear walls (TCSPSWs) with large width-to-height ratios can be increased by adding vertical stiffeners (steel strips). However, the minimum required number of steel strip, which is significant to the practical design of the stiffened TCSPSWs, needs to be investigated. Therefore, a theoretical method of determining the number of steel strips for the stiffened TCSPSWs is introduced. Based on the orthotropic plate theory, the theoretical model of solving the elastic buckling load of the steel-strip-stiffened TCSPSWs is established by utilizing the minimum potential energy theory and Rayleigh-Ritz method. Then the established theoretical model is verified by finite element (FE) models, and the maximum elastic buckling load of the stiffened TCSPSWs is investigated. Subsequently, method of comparing the maximum critical buckling loads of the stiffened TCSPSWs with the corresponding yield loads to determine the minimum required number of steel strips is proposed. Finally, accompanied by providing several calculation examples as illustrations, the method is verified by FE elastoplastic analyses. Results indicated that the proposed method is reliable to be applied to determine the minimum required number of steel strip for the stiffened TCSPSWs in practical engineering.